Zooplankton from a North Western Mediterranean area as a model of metal transfer in a marine environment. (July 2016) - Battuello, M.; Brizio, P.; Mussat Sartor, R.; Nurra, N.; Pessani, D.; Abete, M.C.; Squadrone, S.
Highlights: We monitored the concentration of 21 trace elements in Mediterranean zooplankton. Metal levels showed important variations between seasons and different water depths. Zooplankton can be regarded as a sensitive bioindicator of a large number of trace elements. Zooplankton was found to be a significant accumulator of metals. Abstract: We monitored the concentration of 21 trace elements in zooplankton samples collected in a Northwestern Mediterranean coastal ecosystem (Italy). In the last 20 years, this area has been the target of important anthropogenic impacts including maritime traffic and substantial industrial activities. Zooplankton contributes to the transfer of trace metals to higher trophic levels and constitute one of the recommended groups for the baseline studies of metals in the marine environment. The essential trace elements (As, Cu, Mn, Zn, Fe, Mo, Co, Cr, Se, Ni) and the nonessential trace elements (Al, Be, Cd, Pb, Sb, Sn, V) were generally found at concentrations of no concern in the analyzed zooplankton samples, but showed important variations between seasons and different water depths. The zooplankton was found to be a significant accumulator of metals, and bioaccumulation factors were in the range of 28 (Co) to 10, 9015 (Fe) in marine surficial waters, with increasing values at increasing water depth. Zooplankton is a useful bioindicator to assess metal contamination and its impact in the marine environment.